Empty Space, Open Space. Claiming, Reaching and Remembering Common Ground in Urban Squats. Haga in the 1980’s - Ighe, Ann (PARTECIPAZIONE E CONFLITTO, 2020)
This study focuses on the memories of and narratives about house squatting projects in the late 1980’s, in the Haga neighbourhood in Gothenburg (Göteborg), Sweden by a group of people that came to be known as Husnallarna. This period is critical in terms of constituting a break with an earlier period in Swedish history, defined by social democracy, which came under pressure of strong forces of neoliberalism. One conclusion of the paper is that a group of young people, belonging to a counterculture, rebelled both against the modernist conforming political culture of the welfare state and an expected gentrification, partly by adopting and adjusting to the heritage status of an urban neighbourhood. This heritage status became a part of the identity of the group, and conserving tradition became an act of rebellion, as well as a commoning practice integrating the squatters in the neighbourhood. The study makes use of present-day social media and interviews with activists/squatters.